Evaluation of the safety and efficacy of a biosimilar abobotulinum toxin type A in treating moderate‐to‐severe glabellar lines: A non‐inferiority double blinded randomized controlled trial. (9th April 2022) - Afshani, Seyyedeh Maryam; Samadi, Aniseh; Ayatollahi, Azin; Kashani, Mansour Nassiri; Ahmad Nasdrollahi, Saman; Hosseini, Hamed; Rezagholi, Zahra; Hedayatjoo, Behnaz; Hazegh Fetratjoo, Delara; Ghobadi, Mohammad Amin; Anari, AmirHossein; Saeedifar, Sajjad; et al.
Abstract: Background: Injection of botulinum toxin for cosmetic purposes is a well‐established practice. Objectives: This study was conducted to compare the safety and efficacy of Dyston ® (investigational biosimilar abobotulinumtoxinA) with Dysport ® (abobotulinumtoxinA, Ipsen) in the treatment of moderate‐to‐severe glabellar lines. Methods: Out of 193 screened subjects, 126 volunteers with moderate‐to‐severe glabellar lines fulfilling eligibility criteria were randomized in a 1:1 ratio to receive either an intramuscular injection of 40–60 units of Dyston ® or Dysport ® . The primary objective was to test the non‐inferiority of Dyston ® compared with Dysport ® as measured by the percentage of volunteers who achieved no or mild glabellar lines at maximum frown assessed by the physicians based on the Glabellar Line Severity Score (GLSS) at Day 30. Secondary endpoints included the improvement in the glabellar lines at maximum frown and rest states at Days 14, 60, 90, and 120 as well as the side effects of the treatment. Results: Response rates at maximum frown were 75.44% (43/57) in the Dyston ® group and 76.67% (46/60) in the Dysport ® group on Day 30 ( p value: 0.88, 95% CI: −14.24 to 16.70, diff: 1.23) as per‐protocol set, and were 75.81% (47/62) and 76.19 (48/63) ( p value: 0.96, 95% CI: −14.59 to 15.35, diff: 0.3) in the Dyston ® and the Dysport ® groups, respectively, based on modified intention to treat population. Adverse events were similar in both groups and mostly mild and well‐tolerated. Conclusion: Treatment of moderate‐to‐severe glabellar lines with Dyston ® was effective, tolerable, and non‐inferior compared with Dysport ® .